Antimicrobial Activity of Ethyl Acetate Fraction of Kersen Leaves Against Staphylococcus aureus and Escherichia coli - Weni, Mustika; Marfuati, Sri (Universitas Djuanda, 2024)
The underutilized leaves of the kersen plant contain secondary metabolite compounds that have antibacterial potential. The aim of this research was to test the antibacterial activity of the ethyl acetate fraction of kersen leaf against Escherichia coli and Staphylococcus aureus and determine the best concentration. Kersen leaf extraction method using the maceration method using ethanol solvent, fractionation method using ethyl acetate solvent and testing the antibacterial activity of kersen leaf against Staphylococcus aureus and Escherichia coli using the well diffusion method. The normality test used was the Shapiro-Wilk test and used the One-way Anova parametric statistical test. The results of the phytochemical screening of kersen leaf contain compounds phenols, saponins, tannins, alkaloids and triterpenoids. Concentration of 20% of the ethyl acetate fraction of kersen leaf can inhibit Escherichia coli by 8,817 mm in the medium category and Staphylococcus aureus by 7,987 mm in the medium category. The inhibitory power of the ethyl acetate fraction is higher in inhibiting Escherichia coli than Staphylococcus aureus.